The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5897/jtehs2013.0271
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of toxic effects of chemically and biologically synthesized silver nanoparticles on human gut microflora containing Bacillus subtilis

Abstract: Biological silver nanoparticles were successfully synthesized from a simple green and natural route using the extract of Allium cepa (onion) with the use of silver nitrate as precursor and chemically synthesized using silver nitrate and tri sodium citrate. Nanoparticle synthesis was proven under UV-Visible absorption spectroscopy. Toxicity of sliver nanoparticles was tested using ToxTrak test, in which, fresh overnight broths of Bacillus subtilis and resazurin dye were used to calculate percentage inhibition (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…These color changes and sharp peaks confirm the biosynthesis of colloidal AgNP formation in the solution (Figures 1(a) and 1(b)). In some previous reports, a plasmon peak ranging 400-500 nm in AgNP formation [36] and some reports evident the absorption peak at 350-450 nm for the silver nanoparticles [27]. All in all, some factors such as size and shape of nanoparticles present in the reaction solution may be affecting the SPR absorbance.…”
Section: Resultsmentioning
confidence: 90%
“…These color changes and sharp peaks confirm the biosynthesis of colloidal AgNP formation in the solution (Figures 1(a) and 1(b)). In some previous reports, a plasmon peak ranging 400-500 nm in AgNP formation [36] and some reports evident the absorption peak at 350-450 nm for the silver nanoparticles [27]. All in all, some factors such as size and shape of nanoparticles present in the reaction solution may be affecting the SPR absorbance.…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, in other studied topical application of AgNPs on damaged skin for wound healing purposes in preclinical mouse models were shown produce no toxic effects 38,39 . Furthermore, Tyagi et al, (2013) have reported that AgNPs are biocompatible and friendlier to the human body microflora even after their ingestion 40 . Therefore, our findings together with these previous observations generate enthusiasm for potential future human applications of AgNPs as chemopreventive agents.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its nano-size, NPs can translocate from the entry ports into the circulatory and lymphatic systems, and ultimately to body tissues and organs. Some nanoparticles produce irreversible damage to cells by oxidative stress and/or organelle injury and the extent of which depends on the size and composition of the NPs [216][217][218]. The toxicity of metallic nanoparticles can be due to various reasons, such as dose, size, surface area of nanoparticles, concentration, particle chemistry and crystalline structure, aspect ratio and surface coating and functionalization [217].…”
Section: Environmental Issuesmentioning
confidence: 99%